Uji Aktivitas Antibakteri Air Perasan Jeruk Nipis Terhadap Pertumbuhan Bakteri Staphylococcus epidermidis - Annisa Tri Srilistiany; Erlin Syahril; Zulfahmidah Zulfahmidah; Nurelly Noro Waspodo; Dahlia Dahlia (Yayasan Citra Cendekia Celebes, 2021)
Infectious diseases are one of the health problems in society that are difficult to overcome completely. Bacteria that can cause infectious diseases are Staphylococcus epidermidis bacteria. Diseases caused by bacterial infections are generally treated with antibiotics. The plant that has the potential to be developed as an antibacterial is lime (Citrus aurantifolia swingle). Lime contains flavonoids, phenols, and essential oils that can inhibit the growth of Staphylococcus epidermidis bacteria. To determine the minimum and maximum inhibitory concentrations of lime juice in inhibiting Staphylococcus epidermidis bacteria. Literature review with narrative review design. The literature search was carried out through national journals, international journals, clinical keys, and textbooks for 2016 – 2020. The minimum inhibitory concentration of lime juice which can inhibit the growth of Staphylococcus epidermidis bacteria at a concentration of 20%. While the maximum inhibitory concentration of lime juice which can inhibit the growth of Staphylococcus epidermidis bacteria is at a concentration of 100%. Conclusion: Lime (Citrus aurantifolia swigle) effectively inhibits Staphylococcus epidermidis bacteria.